A Chaconne para violino solo BWV 1004 de J.S. Bach: as poéticas da persuasão - Victor Melo Vale (2011)
This work consists on a study about the Chaconne of the Partita for solo violin BWV 1004, by J.S.Bach. It contains a discussion on the role of rhetoric and the concepts of the affects in Baroque music. This discussion is based on works by Aristotle, Deleuze and Guattari. Founded on this discussion, follows a musical analysis of the Chaconne. The analysis revealed that a prominent trace of this work is the presence of opposing, antithetical occurrences. This was observed in the way in which are employed the modes (minor and major), textures (dense and rarified), sensations of movement (of high and low kinetic energy), melodic contexts (dissonant and consanant) and, especially, the affects (pain-joy; cholera-calmness). Other aspects revealed in the musical analysis are the presence of chiaroscuro technique and musical elements that cause the sensation of time-eternity.